2015
DOI: 10.1128/aac.00390-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Tedizolid and Linezolid against Gram-Positive Cocci Associated with Acute Bacterial Skin and Skin Structure Infections and Pneumonia

Abstract: Tedizolid is a novel, expanded-spectrum oxazolidinone with potent activity against a wide range of Gram-positive pathogens. A total of 425 isolates of Gram-positive bacteria were obtained consecutively from patients with acute bacterial skin and skin structure infections (ABSSSIs) or pneumonia. These isolates included methicillin-susceptible Staphylococcus aureus (MSSA) (n ‫؍‬ 100), methicillin-resistant Staphylococcus aureus (MRSA) (n ‫؍‬ 100), Streptococcus pyogenes (n ‫؍‬ 50), Streptococcus agalactiae (n ‫؍… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
26
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 17 publications
3
26
2
2
Order By: Relevance
“…In addition to these MIC data, in vitro time-kill studies showed that tedizolid had better anti-S. aureus activity than linezolid in that it prevented regrowth at 24 h of incubation. The in vitro findings in this study mirror those in previously published investigations of tedizolid and linezolid activity against S. aureus (9,26). In the present study, we further evaluated the impact of tedizolid versus that of linezolid and vancomycin on biofilm formation in S. aureus and found that exposure of these antibiotics at the MIC to 10ϫ MIC significantly decreased S. aureus biofilm formation.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…In addition to these MIC data, in vitro time-kill studies showed that tedizolid had better anti-S. aureus activity than linezolid in that it prevented regrowth at 24 h of incubation. The in vitro findings in this study mirror those in previously published investigations of tedizolid and linezolid activity against S. aureus (9,26). In the present study, we further evaluated the impact of tedizolid versus that of linezolid and vancomycin on biofilm formation in S. aureus and found that exposure of these antibiotics at the MIC to 10ϫ MIC significantly decreased S. aureus biofilm formation.…”
supporting
confidence: 77%
“…It exerts bacteriostatic microbial activity through inhibition of protein synthesis by binding to the 50S ribosomal subunit of the bacteria. It has been reported that tedizolid is more active against staphylococci and enterococci than linezolid is in vitro (9,10).…”
mentioning
confidence: 99%
“…The study of Chen et al (9) differed from previous studies of tedizolid in the use of an agar dilution method rather than the Clinical and Laboratory Standards Institute (CLSI) reference broth microdilution (BMD) method (11) to determine the susceptibility of tested isolates to tedizolid and linezolid. Furthermore, Chen et al (9) did not provide methodological details concerning the inoculum concentration, the duration of incubation, or the criteria used for MIC endpoint determination.…”
mentioning
confidence: 43%
“…Surprisingly, the Taiwanese isolates of the S. anginosus group were uniformly susceptible to linezolid despite only 38.7% susceptibility to tedizolid (9). Notably, a linezolid-susceptible and tedizolid-resistant phenotype had not been reported in previous in vitro surveillance surveys (1,2,5,8,10).…”
mentioning
confidence: 89%
See 1 more Smart Citation